2020
DOI: 10.1002/mds.28283
|View full text |Cite
|
Sign up to set email alerts
|

Association of PICALM with Cognitive Impairment in Parkinson's Disease

Abstract: Background Cognitive impairment is one of the most disabling nonmotor symptoms in Parkinson's disease (PD). Recently, a genome‐wide association study in Alzheimer's disease has identified the PICALM rs3851179 polymorphism as one of the most significant susceptibility genes for Alzheimer's disease after APOE. The aim of this study was to determine the potential role of PICALM and its genetic interaction with APOE in the development of cognitive decline in PD. Methods A discovery cohort of 712 patients with PD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…According to previous studies, the motor function of idiopathic PD patients were associated with variants in SNCA 36,37 , BST1 38 , ATP8B2 39 , PARK16 40 , and APOE 41 . Additionally, variants of APOE 31,32 , SNCA 42 , TMEM106B 43 , COMT 44 , MAPT 23,44 , PICALM 45 have been found to be associated with variability of cognitive function in idiopathic PD patients. Nevertheless, the associations between genetic variations and clinical features in sporadic PD remain largely elusive and deserved to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, the motor function of idiopathic PD patients were associated with variants in SNCA 36,37 , BST1 38 , ATP8B2 39 , PARK16 40 , and APOE 41 . Additionally, variants of APOE 31,32 , SNCA 42 , TMEM106B 43 , COMT 44 , MAPT 23,44 , PICALM 45 have been found to be associated with variability of cognitive function in idiopathic PD patients. Nevertheless, the associations between genetic variations and clinical features in sporadic PD remain largely elusive and deserved to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Genes and variants initially identified for testing association with clinical parameters were selected based on a prior demonstrated association with PD/parkinsonism or disease progression [MDSgene.org; (10)(11)(12)(34)(35)(36)(37)(38)], or because the gene harbors pathogenic variants that cause PD/parkinsonism [for review, see (39, 40)]. Of 168 variants with a previously reported association and a MAF > 1%, 138 variants (Supplementary Table 2) were present in our data after filtering as described above.…”
Section: Association Testsmentioning
confidence: 99%
“…Iwaki et al (11) demonstrated sex-specific SNP associations with features of the PD phenotype: female patients had a higher risk of developing dyskinesias and a lower risk of developing cognitive impairment. Periñán et al (12) reported an association of the TT genotype at the PICALM SNP rs3851179 with a decreased risk of cognitive impairment in PD. GBA variants have been associated with PD and generally are associated with faster progression and more severe phenotypes (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biology investigations have identified numerous biomarkers and signaling pathways that contribute to PD, including the brain-derived neurotrophic factor (BDNF) [7], histone deacetylase 4 (HDAC4) [8], vacuolar protein sorting 35 (VPS35) [9], leucine-rich repeat kinase 2 (LRRK2) [10], phosphatidylinositol binding clathrin assembly protein (PICALM) [11], RhoA-ROCK signaling pathways [12], Nrf2 signaling pathways [13], GTPase-p38 MAPK signaling pathways [14], JAK/STAT signaling pathway [15] and PI3K/Akt signaling pathway [16]. Further investigation into the molecular events linked with PD is required.…”
Section: Introductionmentioning
confidence: 99%